2015
DOI: 10.1525/abt.2015.77.5.4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Educator & Student Use of & Attitudes toward Dissection & Dissection Alternatives

Abstract: Animal dissection has been routinely practiced in American biology classrooms for decades. With technological advancements, more states adopting student choice measures, and increased awareness about ethical concerns surrounding dissection, many useful dissection alternatives have been developed. To understand the current use of animal dissection and alternatives, and attitudes toward the practices, a nationwide survey of middle and high school biology teachers (n = 1178) and students (n = 500) was conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 5 publications
(5 reference statements)
1
19
0
Order By: Relevance
“…Osenkowski et al. ). Synthetic alternatives to frog tissues may also be used in consideration of the global decline of amphibian species (Edwards et al.…”
Section: Introductionmentioning
confidence: 99%
“…Osenkowski et al. ). Synthetic alternatives to frog tissues may also be used in consideration of the global decline of amphibian species (Edwards et al.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey conducted by the National Anti-Vivisection Society revealed that more than half of educators polled (56%) viewed dissection as an important tradition in biology education. The majority of educators did not believe that alternatives were as good as dissection for teaching anatomy and physiology (54%) and did not believe that technology will make dissection obsolete (59%) (Osenkowski et al, 2015). At the same time, however, our survey revealed that 59% of biology teachers felt that information about dissection alternatives is not widely disseminated (Osenkowski et al, 2015).…”
Section: "Students Using Nonanimal Alternatives Perform As Well As or Better Than Students Using Animal Dissection Specimens"mentioning
confidence: 84%
“…The practice of dissecting animals for biology instruction in American classrooms has a long history, beginning in the 1920s and becoming more widely practiced with the establishment of the Biological Sciences Curriculum Study in the 1960s (Orlans, 1988;NABT, 1990). Recent surveys show that dissection remains a common practice, with ~85% of high school biology teachers offering dissection exercises to their students (Osenkowski et al, 2015;NAVS, 2020). Many animal species, including frogs, pigs, cats, and crayfish, have become regular candidates for dissection, and students often participate in multiple dissections as part of their pre-college science education (Oakley, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While teachers have been commonly found to be comfortable with dissection, students were reported to be relatively more affected, regardless of their nationality. The expressed inclination may range from been emotionally affected to being disgusted (Kavai et al, 2017;Osenkowski, Green, Tjaden, & Cunniff, 2015;Spernjak & Sorgo, 2017). This issue raises the psychological implications of animal experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, many reports indicated that science teachers valued positively both hands-on and virtual variants of dissection, reporting that both variants outcomes were equivalent (Akbarsha et al, 2013;Havlickova et al, 2018;Lalley, Piotrowski, Battaglia, Brophy, & Chugh, 2010). More students than teachers had positive inclination to non-animal alternatives, suggesting an increasing tendency to exchange animal use with alternatives among students (Osenkowski et al, 2015). In this context, it has been proposed that public opinions and associated teachers' and students' attitudes to a substitute of hands-on dissection will slowly change resulting in a gradual reduction of frequency of hands-on dissection and replacement with various kinds of dissection alternatives.…”
Section: Discussionmentioning
confidence: 99%